The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ijinfomgt.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Does knowledge retrieval improves work efficiency? An investigation under multiple systems use

Abstract: Organizations encourage active knowledge retrieval from knowledge management systems; however, this does not always lead to higher work efficiency. Anchoring on uses and gratifications theory and psychology of sunk cost, this study investigates knowledge workers' knowledge retrieval behavior and its subsequent impact on their work efficiency under three knowledge management systems, which differ in the creators of the systems and their related contents. Survey and interview data were collected from an IT call-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Work efficiency refers to the ratio of labor output to time input in an event (Iii et al, 2011). Work efficiency differs from work performance in that efficiency is about the ratio of results to effort, while performance is a specific value that includes results and behavior (Sutanto et al, 2018). Existing research mainly focused on investigating how to improve work efficiency (Lif et al, 2001;Barrett-O'Keefe et al, 2012) and factors that affect work efficiency (Sutanto et al, 2018).…”
Section: Social Media Usage and Work Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Work efficiency refers to the ratio of labor output to time input in an event (Iii et al, 2011). Work efficiency differs from work performance in that efficiency is about the ratio of results to effort, while performance is a specific value that includes results and behavior (Sutanto et al, 2018). Existing research mainly focused on investigating how to improve work efficiency (Lif et al, 2001;Barrett-O'Keefe et al, 2012) and factors that affect work efficiency (Sutanto et al, 2018).…”
Section: Social Media Usage and Work Efficiencymentioning
confidence: 99%
“…However, most of the existing research neglected discussion of how different motivations for social media usage may have an impact on work efficiency and the impact process. Employee work efficiency is the fundamental guarantee for enterprises to obtain profits and realize long-term development (Sutanto et al , 2018). Therefore, it is necessary to investigate the path process between different motivations for different social media platform use and employee work efficiency.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Work efficiency is the ratio of labor output to time invested in an event (Sickles and Zelenyuk, 2019). Previous researches focused on productivity increasement (Liang et al, 2020;Priyadarshini et al, 2020;Vithayathil et al, 2020), and the factors that influenced productivity (Sutanto et al, 2018). Regarding the relationship between social media use and work productivity, studies has shown that work-related social media use could enhance the quality of communication and information exchange among employees, which in turn positively affected their work productivity (Leftheriotis and Giannakos, 2014).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…In the history of knowledge engineering, two kinds of research can be classified: form-oriented research and content-oriented research (Kitamura & Mizoguchi, 2004). The first one focuses on the theory topics like logic, reasoning, retrieval (Sutanto, Liu, Grigore, & Lemmik, 2018), and so on, while the second one investigates the application of the knowledge engineering. Obviously, there has been considerable interest in the former one to date.…”
Section: Introductionmentioning
confidence: 99%